Comparison of the efficacy of QoI fungicides, alone or in mixture with triazoles, in Asian soybean rust control, 2016/17 growing season - Reis,Erlei Melo (2019)
ABSTRACT Evolution has been reported for the reduction in Phakopsora pachyrhizi sensitivity to the mixtures of the three site-specific mechanisms of action (DMIs, QoIs and SDHIs) used in its control. The aim of this study was to quantify the current contribution of QoIs, alone or in mixture with triazoles, in the control of Asian soybean rust. In an experiment carried out in the field, the efficacy of quinone outside inhibitors (QoIs), or strobilurins, was compared for Asian soybean rust control. The isolated effects of four doses of azoxystrobin, picoxystrobin, pyraclostrobin and trifloxystrobin were evaluated, as well as of four applications during the crop cycle. Control by commercial mixtures of these QoIs with triazoles was also compared. Severity was evaluated in four phenological stages, and control was calculated based on final severity data, area under rust progress curve, defoliation, one-thousand-grain mass, grain yield and damage caused by the disease. The lowest mean of rust control efficacy resulted from applications of azoxystrobin (15.8 and 11.19%) and pyraclostrobin (15.4 and 16.76%) and the highest mean was found for picoxystrobin (54.1 and 54.35 %) and trifloxystrobin (69.7 and 64.46%), calculated based on final severity and AUDPC, respectively. Such efficacy is not enough to cover the fungicide application cost, although there was a positive effect of treatments on disease control and grain yield.